3D-Printed Ostomy Flange Stabilizer. Issue 2 (March 2021) - Cosman, Ilan E.; Guillou, Daniel T.; Cosman, Bard C.
Abstract : BACKGROUND: One of the coauthors with tetraplegia (quadriplegia) and a colostomy invented an ostomy flange stabilizer to act as a temporary backplate and aid in pouch changes. DEVICE DEVELOPMENT: In an interactive design process, a 3D-printed ostomy flange stabilizer device was created. The resulting device can be adapted to 3 standard stoma appliance sizes. The stabilizer is reversible, allowing right- and left-handed people to use it on right- or left-sided stomas. Anyone with a 3D printer can print this device from an open-access Web site. CONCLUSION: This device may be of use to many with ostomies and especially those with impaired dexterity. A 3D-printed ostomy flange stabilizer is described. 3D printing allows patient inventions to be disseminated without commercialization.